O consumo hedonista como um reflexo da relação entre valores laborais e pessoais - Gomes, Silmara Cristiane (2016)
individual conflicts, which may help to explain the hedonistic consumer actions, and the specific objectives are: a) identify if the interrelationships between Personal and Labour Values generate individual conflicts; b) identify if individual conflicts, generated by interrelations between Personal and Labour, are predictors of consumer actions. Statistical analyzes were performed to verify the objectives and a literature review was made to enable understanding of the elements that influence the interrelation between Personal Values and Labour Values. Is considered throughout this work, that the hedonistic consumption has gradually been presented as individuals common action and the stimuli that make it happen have changed over the centuries and that these multiple stimuli should be analyzed. This work is dedicated to an aspect of these stimuli